MOBILE PAYMENT TECHNOLOGY FOR FUTURE TRANSACTION - E S Soegoto; S Purna; T P Sumitra (LPPM Universitas Bina Bangsa, 2021)
The development of the Internet and the arrival of e-commerce are driving digitalization in the payment process. This study aims to see the efficiency and effectiveness of the use of mobile payment in all-digital era with rapidly evolving and increasingly sophisticated technology. Financial technology is an innovation in financial services. The method used in this article was a literature study method. The results of this article were that the use of mobile payment was very effective because it was through the touch of finger to make any transaction practically, quickly, and flexibly from a smartphone. The mobile payment method makes it easier to trade electronically. In this case, whether we realize it or not, the payment system with physical money has slowly begun to be abandoned and has generally been switched to mobile payment and electronic cards issued by banks. Mobile payment technology has helped people to pay for anything only through smartphones. This payment method is a step that must be taken to deliver a promising industry in the future